Outcome of COVID19 in Patients With Osteogenesis Imperfecta: A Retrospective Multicenter Study in Saudi Arabia - Alshukairi, Abeer N.; Doar, Hazem; Al-Sagheir, Afaf; Bahasan, Mona A.; Sultan, Anas A.; Al Hroub, Mohammad K.; Itani, Dina; Khalid, Imran; Saeedi, Mohammed F.; Bakhamis, Sarah; Layqah, Laila; Almutairi, Afnan A.; et al. (Frontiers in Endocrinology, 2022)
Background Although genetic diseases are rare, children with such conditions who get infected with COVID-19 tend to have a severe illness requiring hospitalization. Osteogenesis imperfecta (OI) is a rare genetic disorder of collagen resulting in fractures and skeletal deformities. Kyphoscoliosis, restrictive lung disease, and pneumonia worsen the prognosis of patients with OI. The use of bisphosphonate improves bone mineral density (BMD) and reduces fractures in OI. There is no literature describing the impact of COVID-19 in patients with OI. Methodology A retrospective multi-center study was performed in three hospitals in Jeddah and Riyadh, Saudi Arabia, from March 1st, 2020, until August 31st, 2021, aiming to evaluate the outcome of COVID-19 in patients with OI. Demographics, vaccination status, underlying kyphoscoliosis, functional status, use of bisphosphonate, BMD, and COVID-19 severity, and course were recorded for all patients. Results Twelve cases of confirmed COVID-19 were identified among 146 patients with OI. 9 (75%) of patients were less than 18 years, 6 (50%) were male, 5 (41%) had kyphoscoliosis, and 5 (41%) were wheelchair-bound. 6 (50%) received bisphosphonate, and 7(58%) had normal BMD. All patients had mild disease and did not require hospitalization. None of OI the patients with COVID-19 were fully vaccinated before the infection, and some were ineligible for vaccination. Conclusion Patients with OI and COVID-19 in our study recovered without complications, unlike patients with other genetic diseases. Young age and mild illness contributed to the favorable outcome. Half of the patients received bisphosphonate and had normal BMD.